The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fendo.2022.893901
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive factors and cognitive impairment in natural menopausal women: A cross-sectional study

Abstract: IntroductionLittle information on rural older women in northern China has been reported, apart from three studies in southern and eastern China in the past decade. This study aims to evaluate the relationships between reproductive factors and the risk of cognitive impairment, including mild cognitive impairment (MCI) and dementia, in Chinese women with natural menopause.MethodsThe cross-sectional study was conducted in 112 community primary healthcare centers in rural northern China between April 2019 and Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…E2 is important for regulating hippocampal learning and memory. With the increase of subjective cognitive dysfunction and elevated rates of depression in this period, premature estrogen decline can lead to mild cognitive impairment (MCI), even Alzheimer's disease (AD), dementia with Lewy bodies (DLB) and vascular dementia (VaD) [ 80 , 81 ]. However, as continued interest and debate, whether the MHT cure or prevent cognitive impairment or not.…”
Section: Discussionmentioning
confidence: 99%
“…E2 is important for regulating hippocampal learning and memory. With the increase of subjective cognitive dysfunction and elevated rates of depression in this period, premature estrogen decline can lead to mild cognitive impairment (MCI), even Alzheimer's disease (AD), dementia with Lewy bodies (DLB) and vascular dementia (VaD) [ 80 , 81 ]. However, as continued interest and debate, whether the MHT cure or prevent cognitive impairment or not.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MCI and dementia was studied to be 28.6% and 11.4% in older women, respectively. Younger age at menopause, shorter childbearing years, greater age at menarche, and greater number of pregnancies/births were correlated with poor cognition and significantly increased the risk of MCI and dementia, especially AD, DLB, and VaD [84].…”
Section: Reproductive Period and Risk Of Dementiamentioning
confidence: 97%
“…Ovarian aging is the ongoing process of decline and the eventual depletion of ovarian function [4]. It not only leads to a reduced reproductive capacity, fertility, and menopausal syndromes, but also increases the risk of aging-related diseases such as osteoporosis, cognitive impairment, cardiovascular disease, and cancer [5][6][7][8]. It has been shown that all-cause mortality and cancer rates are higher in the premature ovarian failure (POF) population than in the normal menopausal age group [9].…”
Section: Introductionmentioning
confidence: 99%